2022
DOI: 10.1111/jeb.14022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cis‐sex chromosome transition in banded geckos (Coleonyx, Eublepharidae, Gekkota)

Abstract: Sex‐determination systems are highly variable amongst vertebrate groups, and the prevalence of genomic data has greatly expanded our knowledge of how diverse some groups truly are. Gecko lizards are known to possess a variety of sex‐determination systems, and each new study increases our knowledge of this diversity. Here, we used RADseq to identify male‐specific markers in the banded gecko Coleonyx brevis, indicating this species has a XX/XY sex‐determination system. Furthermore, we show that these sex‐linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…The absence of transcriptional repression of any specific pair of chromosomes during pachytene (no antibodies against γH2AX yielded any positive staining) suggested that meiotic sex chromosome inactivation (MSCI) was absent in the four reptilian species, contrasting male mammals ( Turner et al, 2005 ; Ruiz-Herrera and Waters, 2022 ). The absence of MSCI is not surprising because our reptile models either do not have sex chromosomes (the painted turtle, Valenzuela et al, 2014 ), or because males are the homogametic sex (the bearded dragon, Ezaz et al, 2005 ), or because sex chromosomes are likely poorly differentiated (the ocelot gecko and the western banded gecko, Keating et al, 2022 ; Rovatsos et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of transcriptional repression of any specific pair of chromosomes during pachytene (no antibodies against γH2AX yielded any positive staining) suggested that meiotic sex chromosome inactivation (MSCI) was absent in the four reptilian species, contrasting male mammals ( Turner et al, 2005 ; Ruiz-Herrera and Waters, 2022 ). The absence of MSCI is not surprising because our reptile models either do not have sex chromosomes (the painted turtle, Valenzuela et al, 2014 ), or because males are the homogametic sex (the bearded dragon, Ezaz et al, 2005 ), or because sex chromosomes are likely poorly differentiated (the ocelot gecko and the western banded gecko, Keating et al, 2022 ; Rovatsos et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The three lizards have genotypic sex determination (GSD). The bearded dragon has ZW sex chromosomes ( Ezaz et al, 2005 ; Koubová et al, 2014 ), whereas the western banded gecko and the ocelot gecko GSD systems are still unknown ( Rovatsos et al, 2019 ; Keating et al, 2022 ). However, the genetic sex determination of the bearded dragon can be overridden by temperature to produce viable ZZ females ( Quinn et al, 2007 ; Holleley et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in this special issue: Using a combination of short‐read and long‐read sequencing, Evans et al (2022) and Duhamel et al (2022) perform a chromosome‐scale genome assembly in the Marsabit clawed frog and anther‐smut fungi, respectively. These approaches allow the study of intra‐specific variation of sex chromosome divergence in the frog and reveal independent chromosomal rearrangement in the mating‐type chromosomes of the fungi. With short‐read WGS and the help of existing reference genomes, Sigeman et al (2022) investigate the translocation nature of a novel neo‐sex chromosome in Sylvivoidea songbirds, whilst Rovatsos et al (2022) reveal a XX/XY sex determination system in a blind lizard and further identified a novel combination of homologous genes using the chicken X chromosome as reference. With short‐read whole‐genome pooled sequencing, Ansai et al (2022) and Jeffries et al (2022) investigate the sex‐determining regions and sex chromosome turnover across closely related fish taxa. With RAD‐seq, Keating et al (2022) and Meuser et al (2022) perform analysis in multiple individuals per sex to investigate possible sex‐determining regions and infer sex chromosome turnovers. …”
Section: Theme 1: Genomics and Methodological Advancesmentioning
confidence: 99%
“…In a small minnow, the common creek chub, Meuser et al (2022) find almost zero sex‐linked markers with a RAD‐seq approach, providing insights into the limitations of this technique for species with poorly differentiated sex chromosomes. Applying a similar RAD‐seq pipeline, Keating et al (2022) successfully identify male‐specific markers in a banded gecko, suggesting the presence of a XX/XY sex chromosome system. The authors further demonstrated a sex chromosome turnover from an XY to another XY system in the banded geckos of the genus Coleonyx .…”
Section: Theme 4: Detection Of Sex‐determining Genes and Sex Chromoso...mentioning
confidence: 99%
“…For example, in a species with an XY system, an autosome can become a proto‐X/proto‐Y chromosome pair with the acquisition of a male‐determining locus (e.g. Keating et al, 2022). The ancestral X and/or Y chromosome can subsequently revert to an autosome, as has been observed in Drosophila (Carvalho & Clark, 2005; Larracuente et al, 2010; Vicoso & Bachtrog, 2013).…”
Section: Sex‐specific Selection and The Evolution Of Sex Chromosomesmentioning
confidence: 99%